Akal Rohani Imitasi di Realitas Gereja Virtual: Sebuah Pneumatologi Eklesial Komuni - Josua Estomihi Butarbutar (Asosiasi Teolog Indonesia, 2026)
This article proposes an ecclesial communion pneumatology as a theological framework for a virtual church that operates through artificial intelligence (AI) and virtual reality (VR). Specifically, it answers the ontological and theological questions pertaining to whether the Holy Spirit is present and works in digital liturgy mediated by technologies, as well as how AI might be an instrument for genuine personal connectedness. This research employs a transdisciplinary descriptive qualitative method drawing from John Zizioulas’s ecclesial communion, Amos Yong’s theology of participation, and discourses on vanity and theopoetics, articles on AI and VR, church documents, and metaverse studies. The author’s reflection oscillates among the aesthetics of digital sacred space, contemporary spirituality, and cultural critiques. The result is an understanding of the Holy Spirit that constitutes the church in her relational and ecstatic “mode of being,” therefore provoking an idea of the digital medium (AI/VR) as a space where the Spirit establishes ecclesial hypostasis—the church’s identity no longer identified by spatial and physical limits—insofar as such a medium facilitates, not substitutes for, personalized love relations. The virtual church, as this article concludes, must be perceived in terms of a new expression of the communion reality that is already present in the God of the Trinity